KARYOLOGY OF SEVEN TRIFOLIUM L. TAXA GROWING IN TURKEY - Kiran, Yasar; Sahin, Ahmet; Turkoglu, Ismail; Kursat, Murat; Emre, Ifran (Polska Akad Nauk, Polish Acad Sciences, Pas Branch Cracow, 2010)
The paper reports karyomorphometric features and somatic chromosome numbers for seven Trifolium L. taxa. Three basic chromosome numbers are identified (x=5, 7, 8). Trifolium speciosum Willd. and Trifolium physodes Stev. ex Bieb. var. physodes have somatic chromosome number 2n=16; Trifolium campestre Schreb.. Trifolium pratense L. var. americanum Harz and Trifolium sylvaticum Gerard ex Lois. have 2n=14; Trifolium bocconet Savi has 2n=10; and Trifoiium repens L. var. repens is tetraploid 2n=32. All chromosomes have the centromeres at the median point (M) or median region (m) except for one chromosome of Trifolium sylvaticum Gerard ex Lois, which is submetacentric (sm). The only satellite observed was in the genome of Trifolium bocconei Savi.
Keywords: Chromosome numbers; karyotype; Trifolium L.